2017
DOI: 10.18097/pbmc20176303241
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of neuronal nicotinic acetylcholine receptors in compensatory brain mechanisms at early stages of Parkinson's disease

Abstract: A role of nicotinic acetylcholine receptors (nAChR) in the development of Parkinson's disease (PD) has been investigated using two mouse models corresponding to the presymptomatic stage and the early symptomatic stage of PD. Quantitative determination of nAChR in the striatum and substantia nigra (SN) was performed using the radioactive derivatives of epibatidine, -conotoxin MII, and -bungarotoxin as ligands. The number of ligand-binding sites changed differently depending on their location in the brain, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Investigating 3FTXs are not only of interest to characterize their toxicity, but also of great significance for structural studies, as well as for biotechnological, biomedical and evolutionary studies [ 59 , 60 , 61 , 62 , 63 ]. Already, 3FTXs have proven to be an efficient tool to analyze various receptor types, and to study diseases like Parkinson’s disease, myasthenia gravis and cancer [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. The aminergic toxins from mamba venom served as good candidates for protein resurrection methodology [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigating 3FTXs are not only of interest to characterize their toxicity, but also of great significance for structural studies, as well as for biotechnological, biomedical and evolutionary studies [ 59 , 60 , 61 , 62 , 63 ]. Already, 3FTXs have proven to be an efficient tool to analyze various receptor types, and to study diseases like Parkinson’s disease, myasthenia gravis and cancer [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. The aminergic toxins from mamba venom served as good candidates for protein resurrection methodology [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of the invariant Cys-loop Asp residue, in the acetylcholine receptor δ-subunit was identified in a patient suffering from congenital myasthenia syndrome [ 77 ]. A recent study employing the use of radioactive derivative of α-bungarotoxin suggested the possible function of neuronal nAChR in the development of Parkinson’s disease [ 78 ]. Apart from serving as molecular probes in various medical disorders, three-finger neurotoxins are also gaining attention as potential analgesics, anti-inflammatory molecules, and immunosuppressant [ 79 ].…”
Section: Snake Venom Peptides and Their Potential Pharmacological mentioning
confidence: 99%